The impact of emotion on the formation of customers’ repeat visit intentions in the lodging industry - Han, Heesup (Kansas State University, 2005)
The objectives of this research were to address the impacts of positive and negative emotions on customers’ satisfaction and customers’ repeat visit intentions, and to investigate the mediating effect of customer satisfaction on the relationship between emotion and customers’ repeat visit intentions. A theoretical model of the formation of repeat visit intentions was proposed through a comprehensive review of the literature. Richins’ Consumption Emotion Set (1997) was modified to make it suitable for application in the lodging industry. The modifications were based on the participants’ responses to each emotion descriptor in the pilot test. Surveys were completed by graduate students and faculty members, undergraduate students at a Midwestern university, and conference attendees. Of 259 surveys returned, 248 responses were used for data analysis. Data were analyzed using factor analysis and a series of regression analysis. Positive and negative consumption emotions were found to have a significant effect on customer satisfaction and repeat visit intentions. Results also provided evidence of a significant association between customer satisfaction and repeat visit intentions. Customer satisfaction was found to be a full mediator in the relationship between customers’ positive and negative consumption emotions and repeat visit intentions. The loss aversion of the prospect theory was empirically supported in the formation of customers’ repeat visit intentions since results indicate that negative emotion has a greater influence on customer satisfaction and customers’ repeat visit intentions. Results support the importance of considering the impact of customers’ emotions on post-purchasing behaviors when developing better marketing and service strategies to achieve higher occupancy rate and retain customers.
Keywords: Consumption emotion; Customer satisfaction; Lodging industry; Repeat visit intention; Business Administration, Management (0454)Business Administration, Marketing (0338)